GMS current posters in otorhinolaryngology, head and neck surgery (Deutsche Gesellschaft für Hals-Nasen-Ohren-Heilkunde, Kopf- und Hals-Chirurgie ; GMS, 2005)
GMS current posters in otorhinolaryngology, head and neck surgery presents the posters (PDF) and the poster abstracts of the annual meetings of the German Society of Otorhinolaryngology, Head and Neck Surgery.